The crystal structure of tetrakis(4-allyl-2-methoxyphenyl nicotinato-k 1 N)bis(thiocyanato-k 1 N)cobalt(II) - Wang Lei; Liu Zhen-Xiang; Cai Shuping (Zeitschrift für Kristallographie - New Crystal Structures)
C66H60CoN6O12S2, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 9.2930(4) Å, b = 12.7458(6) Å, c = 13.7934(7) Å, α = 98.895(2)∘, β = 97.231(2)∘, γ = 95.445(2)∘, V = 1590.36(13) Å3, Z = 1, R gt(F) = 0.0469, wR (F 2) = 0.1388, T = 298 K.